Virus-Induced Changes of the Respiratory Tract Environment Promote Secondary Infections With Streptococcus pneumoniae - Sender, Vicky; Hentrich, Karina; Henriques-Normark, Birgitta (Frontiers in Cellular and Infection Microbiology, 2021)
Secondary bacterial infections enhance the disease burden of influenza infections substantially. Streptococcus pneumoniae (the pneumococcus) plays a major role in the synergism between bacterial and viral pathogens, which is based on complex interactions between the pathogen and the host immune response. Here, we discuss mechanisms that drive the pathogenesis of a secondary pneumococcal infection after an influenza infection with a focus on how pneumococci senses and adapts to the influenza-modified environment. We briefly summarize what is known regarding secondary bacterial infection in relation to COVID-19 and highlight the need to improve our current strategies to prevent and treat viral bacterial coinfections.